Experimentation of Magnetorheological Piston Damper - Borhan N.; Jaafar M.F.; Rahiman W. (Springer Science and Business Media Deutschland GmbH, 2023)
Damping; Magnetic fields; Permanent magnets; Sedimentation; Testing; Fluid mixtures; Magnetic-field; Magnetorheological; Mr dampers (Magneto Rheological); Performance; Property; Safety precautions; Static tests; Magnetorheological fluids